From Toxoplasmosis to Schizophrenia via NMDA Dysfunction: Peptide Overlap between Toxoplasma gondii and N-Methyl-d-Aspartate Receptors As a Potential Mechanistic Link - Lucchese, Guglielmo (Frontiers in Psychiatry, 2017)
The present work aims at investigating how Toxoplasma gondii (T. gondii) infection may be linked to N-Methyl-D-Aspartate receptors (NMDARs) dysfunction in schizophrenia and related disorders and puts forward the hypothesis that immune responses against T. gondii may involve NMDAR receptors. Indeed, the analysis of the protozoan proteome and NMDAR subunits for peptide commonalities shows a massive peptide overlap and supports the possibility that anti-T. gondii immune responses raised during active protozoan infection may crossreact with host NMDARs, determining disruption of neural circuits and cognitive deficits. In particular, the NMDA 2D subunit, which is mainly expressed in parvalbumin-positive interneurons, appears to be a hotspot for potential T. gondii-induced immune crossreactive attacks.